2017
DOI: 10.19082/4497
|View full text |Cite
|
Sign up to set email alerts
|

The association between parental mental health and behavioral disorders in pre-school children

Abstract: Background and AimBehavioral disorders among children reflect psychological problems of parents, as mental illness of either parent would increase the likelihood of mental disorder in the child. In view of the negative relationship between parents’ and children’s illness, the current study intended to determine the correlation between mental health of parents and behavioral disorders of pre-school children.MethodsThe present descriptive-correlational research studied 80 children registered at pre-school center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
0
11
0
10
Order By: Relevance
“…The association between parental and child psychiatric disorders has been well established by previous researchers [ 20 , 35 ]. Concerning our study, the results suggested the existence of significant associations between maternal and child psychopathological symptoms through a full mediation of parenting practices, as previous research proposed [ 17 ].…”
Section: Discussionmentioning
confidence: 97%
“…The association between parental and child psychiatric disorders has been well established by previous researchers [ 20 , 35 ]. Concerning our study, the results suggested the existence of significant associations between maternal and child psychopathological symptoms through a full mediation of parenting practices, as previous research proposed [ 17 ].…”
Section: Discussionmentioning
confidence: 97%
“…In light of this scenario, an adequate support network for the children is necessary. Such children also perceive the importance of social support, especially from mental health professionals, considering that they live together with parents who have mental problems (Drost & Schippers, 2015;Drost, van der Krieke, Sytema, & Schippers, 2016;Karimzadeh, Rostami, Teymouri, Moazzen, & Tahmasebi, 2017;Rodrigues & Nogueira, 2016;Schoen, 2016;Yamamoto & Keogh, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the parents' anxiety and stress are associated with the child's irritability, and vice versa. Accordingly, observing this mutual vulnerability in the mother-child relationship makes it possible for pediatric health professionals to identify the mental health problems existing in the child's environment (Drost & Schippers, 2015;Drost et al, 2016;Karimzadeh et al, 2017;Kingsbury, Clavarino, Mamun, Saiepour, & Najman, 2017;Pratta & Santos, 2007;Yamamoto & Keogh, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The physical and mental health of the future child is determined by the health of both parents (Chiarlitti & Kolen, 2017;Karimzadeh et al, 2017;Boardman et al, 2012). The health of women around the conception period is now a topic of high interest, reflected in several reports from international agencies (Davies, 2015;Johnson et al, 2012;Hanson et al, 2015;.…”
Section: Obesity Life Cyclementioning
confidence: 99%